QUALIDADE FÍSICO-QUÍMICA E MICROBIOLÓGICA DE GRÃOS DE MILHO NO ARMAZENAMENTO INFESTADOS COM Sitophilus zeamais - Paloschi, Cristiane Lurdes (2014)
This work aimed to study the effects of infestation of insects Sitophilus zeamais on the physicochemical and microbiological quality in corn kernels during storage. For the experiment, samples of hybrid maize (Zeamays) were collected from cultivar Dow 2B512Hx, grown in western Paraná, harvested in June / July 2013. For storage, the grains had water contents below 15% bs, and about 300g of them were stored in glass containers closed with tissue type Voil to facilitate gas exchange, with a total of 40 containers stored in a BOD incubator at a temperature of 27±1 °C for 180 days. From all the recipients, 20 were infested with 20 adult insects of Sitophilus zeamais and the other 20 were kept uninfested. Every 45 days, samples were taken and physical and chemical analyzes were carried out (grain weight loss, population variation of insects, classification of corn, mass of 1000 seeds, water content, ash, oil, protein and carbohydrates and dietary fiber total), as well microbiological analyzes (counting of filamentous fungi and identification of aflatoxin-producing fungi) and quantitation of aflatoxin (B1, B2, G1 and G2). Exploratory analysis of the response variables was done by use of the analysis of variance (ANOVA) and mean comparison test was performed by Tukey's test with a significance level of 0.05. The final grain weight in dry material with insects reduced in the course of time, what increased the losses in grain mass and showed statistically significant differences. The population of insects and the classification of maize also showed statistically significant differences. It was observed that when storage time increased, the population of insects also increased and the percentage of whole grains reduced for both storage conditions. The content of water, protein and filamentous fungi incidence increased in grains initially infested during storage, and the 1000 grains weight, the content of carbohydrates and total dietary fiber content in these grains decreased compared to uninfected grains. The incidence of aflatoxin was not detected in maize kernels during the studied storage period. Finally, from these results, it is possible to conclude that the longer the period of contact of insects with the largest grains, larger the damages and losses to producers are. However, S. zeamais did not behave as a mechanical vector of the fungus Aspergillus ssp., with no correlation between the incidence of filamentous fungi and the level of aflatoxins (B1, B2, G1 and G2).